Sport specialization and overuse Injuries in adolescent throwing athletes: A narrative review - Zaremski, J. L.; Zeppieri Jr., G.; Tripp, B. L. (Journal of Athletic Training, 2019)
A significant number of adolescent athletes throughout the world participate in various throwing-dominant sports, including but not limited to baseball, cricket, handball, softball, track and field throwing events, and water polo. Due to the unique stresses placed on the throwing arm and entire body in these sports, a robust volume of literature has highlighted concerns about sport specialization in these athletes and an associated increased risk of injury, particularly to the dominant shoulder and elbow, with sport specialization. This review will highlight the evidence-based literature for this athletic niche, focusing on risk factors for injury, national and international organizations' recommendations for limiting overuse injuries, principles of conditioning and rehabilitative programs, and potential future areas of research to curb the growing incidence of throwing-related injuries among adolescent throwing athletes.